Integration Rice Price And Farmers Welfare With Error Correction Model Analysis - Makbul, Yogi (Archives of Business Research, 2019)
This research analyzes the short- and long-term influence of rice prices on the welfare of Indonesian farmers using an error correction model. Drawing upon data from Indonesia's Central Bureau of Statistics, it reveals that rice prices exert significant positive short-run effects and no significant long-run influence on farmers' welfare. These findings extend or refine results from earlier studies that lack the time series perspective of our research. They also support policy intervention by the Indonesian government to increase farmers' welfare and assure food supply.